Brimonidine Eye Drops within the Reach of Children: A Possible Foe - Daniela Trotta; Mirco Zucchelli; Carmela Salladini; Patrizia Ballerini; Claudia Rossi; Maurizio Aricò (MDPI AG, 2024)
Brimonidine, a selective alpha-2 adrenergic agonist used for the treatment of open-angle glaucoma, has been shown to cause neurological side effects such as unresponsiveness, lethargy, hypoventilation, and stupor, mimicking opioid toxicity. We report one case of transient encephalopathy in a toddler, in whom accidental brimonidine toxicity was suspected and then confirmed by a toxicology study. The healthy 8-month-old girl was taken to the pediatric ER since she was drowsy and hypotonic with miosis. The computed tomography scan of her brain and toxicological workup of her blood and urine were negative. Starting from the fourth hour, the child progressively improved, and by the sixth hour, she recovered to a normal state of consciousness. A survey of available drugs within the child's reach showed the presence of brimonidine. Thus, ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was applied to quantify the brimonidine in urine and plasma samples, showing levels of 8.40 ng/mL and 0.79 ng/mL, respectively. To our knowledge, this is the first report to determine brimonidine levels in urine and plasma using UPLC-MS/MS. Insufficient knowledge on the part of family members about the potential hazards of an apparently innocuous, topical medication such as eye drops may put children at a greater risk of poisoning. Necessary warnings should be given to parents with greater care when prescribing this medication.